2011
DOI: 10.1096/fj.11-182360
|View full text |Cite
|
Sign up to set email alerts
|

Tandem reporter assay for myristoylated proteins post‐translationally (TRAMPP) identifies novel substrates for post‐translational myristoylation: PKC∊, a case study

Abstract: Myristoylation, the addition of a 14-carbon fatty acid to the N-terminal glycine of a protein, is key to protein-membrane and protein-protein interactions. Typically, myristoylation occurs cotranslationally; however, post-translational myristoylation of caspase-cleaved proteins is now emerging as a well-established protein modification and as a novel regulator of apoptosis. To identify additional post-translationally myristoylated proteins, we engineered a plasmid vector encoding for a caspase-cleavable report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 62 publications
1
31
0
Order By: Relevance
“…Of note, blocking caspase cleavage at D586 completely reverses the disease phenotype in the YAC128 HD mouse model [24]. In addition, we have shown that HTT is PTMyr at G553 following caspase cleavage at D552 [6,25] (Figure 2A). …”
Section: Post-translational Myristoylation At the Crossroads Of Caspamentioning
confidence: 74%
See 2 more Smart Citations
“…Of note, blocking caspase cleavage at D586 completely reverses the disease phenotype in the YAC128 HD mouse model [24]. In addition, we have shown that HTT is PTMyr at G553 following caspase cleavage at D552 [6,25] (Figure 2A). …”
Section: Post-translational Myristoylation At the Crossroads Of Caspamentioning
confidence: 74%
“…It has also become apparent that caspases are required for multiple processes including cell survival, proliferation and differentiation [16,17], suggesting that PTMyr is not restricted to just apoptosis, but may be a constitutive process that provides a dual function and an additional layer of regulation for proteins following caspase cleavage during various cell pathways. This is supported by the fact that the overexpression of myristoylated C-terminal-truncated (myr-ct) gelsolin and myr-ctPKCε are implicated in cell survival [6,18] compared with myr-ctBID and myr-ctPAK2 [1,7], which promote cell death. This is supported by the fact that the overexpression of myristoylated C-terminal-truncated (myr-ct) gelsolin and myr-ctPKCε are implicated in cell survival [6,18] compared with myr-ctBID and myr-ctPAK2 [1,7], which promote cell death.…”
Section: The Two Faces Of Post-translational Myristoylationmentioning
confidence: 99%
See 1 more Smart Citation
“…3). Because the half-life/photostability of the reporter proteins is 24–48 h for lacZ and 1 h for tdTomato (Martin et al, 2012; Smith et al, 1995), the protein marker expression observed in these studies represents the true transcription of the gene.…”
Section: Validation Of the Cre-directed Mgp Expressionmentioning
confidence: 99%
“…For many years, myristoylation was thought to occur only cotranslationally, until the C‐terminal fragment of caspase‐truncated Bid (ctBid) was demonstrated to be post‐translationally myristoylated during apoptosis (10). Since then, work done by the laboratories of Utsumi (11, 12) and ours (13, 14) have identified the caspase‐cleaved C‐terminal products of actin (11), gelsolin (12), p21‐activated kinase 2 (PAK2) (ref. 13), and PKCε (14) to be post‐translationally myristoylated.…”
mentioning
confidence: 99%